A Review On: Exploration of Wild Edible Plants - Sanket P. Gawali,; Kulbhushan W. Pawar, (International Journal of Scientific Research in Science and Technology, 2025)
Since the beginning of time, people have been gathering Wild Edible Plants (WEPs,) and they are now a staple of the human diet and conventional food systems. When food crops are few, WEPs continue to be crucial for maintaining food security and sovereignty, as well as having the potential to improve the well-being of non-significant households. The most popular Non-Timber Forest Products (NTFPs) are a Wild Edible Fruits (WEFs), which are also significant sources of revenue, medicine, and nourishment for those who use them. Besides being used as food, WEF species can produce fibre, fuel, and various processed goods. Farmers and breeders can cross them with domesticated crops to create new types because they have a variety of traits, such as drought tolerance and pest resistance. They contribute to enhancing the product's nutritional value and productivity. Furthermore, more research is needed to investigate the therapeutic potential and nutritional value of WEPs to provide a scientific foundation for further development of the herbal medicines and traditional foods, considering a above need review study was undertaken.
Keywords: Exploration; Wild edible; Nutritional; Traditional